2021
DOI: 10.1111/1460-6984.12676
|View full text |Cite
|
Sign up to set email alerts
|

Intervention for oral language comprehension skills in preschoolers with developmental language disorder

Abstract: Background There is a clear predominance of programmes aimed at improving aspects related to language production in pupils with developmental language disorder (DLD). However, programmes aimed at improving their receptive skills are limited. Aims The main aim was to assess the effectiveness of an intervention programme for oral language comprehension skills in preschoolers with typical development (TD) and pupils with DLD. Methods & Procedures Participants were 99 five‐year‐old pupils, with and without DLD, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…However, these reviews were mostly based on studies of children with TD [23][24][25][26][27]. In contrast, our findings add to more recent studies reporting far transfer to language performance, usually with children who have developmental conditions such as language difficulties [29,[35][36][37][38][39]. It is notable that the present study achieved these positive outcomes following training on just two executive working-memory tasks (one verbal and one visuospatial) administered in 18 sessions of around 10 min three times a week (total 3 h).…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…However, these reviews were mostly based on studies of children with TD [23][24][25][26][27]. In contrast, our findings add to more recent studies reporting far transfer to language performance, usually with children who have developmental conditions such as language difficulties [29,[35][36][37][38][39]. It is notable that the present study achieved these positive outcomes following training on just two executive working-memory tasks (one verbal and one visuospatial) administered in 18 sessions of around 10 min three times a week (total 3 h).…”
Section: Discussionmentioning
confidence: 45%
“…Delage et al [39] used the same Magic Memory intervention, reporting improved working memory in DLD and TD groups compared to active control groups immediately post-intervention, with additional far-transfer gains on sentence repetition and complex syntax in the DLD intervention group. Therefore, the findings reported since 2018 are not only promising support for working-memory interventions for children with DLD, but also suggest that children with DLD may gain more from working-memory interventions compared to individuals with TD [24,[34][35][36][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen RCTs (18 articles) compared an intervention for speech and language delay or disorders with an inactive control (no treatment or wait-list control/delayed treatment) . Study characteristics are shown in eTable 11 in the Supplement.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen RCTs (18 articles) compared an intervention for speech and language delay or disorders with an inactive control (no treatment or wait-list control/delayed treatment). [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] Study characteristics are shown in eTable 11 in the Supplement. No studies enrolled children identified by routine screening in primary care.…”
Section: Benefits Of Treatmentmentioning
confidence: 99%
“…One noteworthy finding from this study was that IQ scores of all the subtests and indices in WISC of DSLDs children were significantly lower than TD children and WMI was the most severe impaired index for DSLDs individuals. As far as we are concerned, few previous studies systemically explored the intelligence profile of children with DSLDs ( 34 , 35 ). Our study comprehensively displayed the cognitive characteristics of DSLDs, suggesting DSLDs affect multiple learning abilities at childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%